Protection of Two and Three mRNA Vaccine Doses Against Severe Outcomes Among Adults Hospitalized With COVID-19—VISION Network, August 2021 to March 2022. (23rd November 2022) - DeSilva, Malini B; Mitchell, Patrick K; Klein, Nicola P; Dixon, Brian E; Tenforde, Mark W; Thompson, Mark G; Naleway, Allison L; Grannis, Shaun J; Ong, Toan C; Natarajan, Karthik; Reese, Sarah E; Zerbo, Ousseny; et al.
Abstract: Background: We assessed coronavirus disease 2019 (COVID-19) vaccination impact on illness severity among adults hospitalized with COVID-19, August 2021–March 2022. Methods: We evaluated differences in intensive care unit (ICU) admission, in-hospital death, and length of stay among vaccinated (2 or 3 mRNA vaccine doses) versus unvaccinated patients aged ≥18 years hospitalized for ≥24 hours with COVID-19–like illness and positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) molecular testing. We calculated odds ratios (ORs) for ICU admission and death and subdistribution hazard ratios (SHR) for time to hospital discharge adjusted for age, geographic region, calendar time, and local virus circulation. Results: We included 27 149 SARS-CoV-2–positive hospitalizations. During both Delta- and Omicron-predominant periods, protection against ICU admission was strongest among 3-dose vaccinees compared with unvaccinated patients (Delta OR, 0.52 [95% CI, .28–.96]; Omicron OR, 0.69 [95% CI, .54–.87]). During both periods, risk of in-hospital death was lower among vaccinated compared with unvaccinated patients but ORs overlapped across vaccination strata. We observed SHR >1 across all vaccination strata in both periods indicating faster discharge for vaccinated patients. Conclusions: COVID-19 vaccination was associated with lower rates of ICU admission and in-hospital death in both Delta and Omicron periods compared with being unvaccinated. Abstract : COVID-19 vaccination was associated with lower rates of ICU admission and in-hospital mortality during both Delta and Omicron predominance compared with being unvaccinated. COVID-19 vaccines attenuate disease severity in patients hospitalized with symptomatic SARS-CoV-2 infection.